Evaluation of the use of the bedding function of City Clinical Hospital No. I. Pirogov during the period 2012–2021 based on statistical indicators - N. V. Shakhova (Здоровье мегаполиса, 2022)
Relevance. The importance of efficient use of internal resources in health care is recognized at all levels of health management. An analysis of the indicators of the bed fund in dynamics makes it possible to assess the resources of a medical organization, identify problematic aspects in time and develop a set of measures aimed at eliminating errors and optimizing the work of the institution.Purpose of the study. Evaluation of the performance indicators of the round-the-clock hospital of the City Clinical Hospital No. 1 named after N. I. Pirogov in the period 2012–2021 in order to improve the efficiency of the medical organization.Materials and methods. To achieve the goal of the study, the obtained material was processed using analytical and statistical methods. Indicators of the use of the bed fund of the City Clinical Hospital No. 1 named after N. I. Pirogov for 2012–2021, necessary for calculations, were taken from table 3100 of the Federal statistical Obstrvation form No. 30 "Information on a medical organization". The calculation of indicators was carried out on the basis of methodological recommendations on the application of standards and norms of resource provision of the population in the healthcare sector [1].Results and discussions. To assess the effectiveness of a medical organization providing care in a hospital, 4 main indicators of the use of the bed fund were used. The results of the average annual bed occupancy showed that the highest level of the indicator falls on 2014 (404 days), and the lowest on 2021 (278 days). The indicator tended to decrease by 24 % and amounted to 278 days by 2021, which indicates a pronounced intensification of the treatment process. The bed turnover indicators indicate a pronounced intensification of the treatment process. The greatest intensification was recorded in 2021 (43,9 patients per 1 bed) and amounted to 129 %. In general, the bed turnover indicators for the hospital in the period from 2012–2021. had an upward trend. An analysis of the bed turnover clearly showed that a two-fold excess of the standard significantly affected the average duration of the patient's stay in bed. In 2012, the indicator was 10,5 days. In subsequent years, the indicator tended to decrease and by 2021 reached the level of 4,9 days. The results of the analysis of bed downtime show that the most downtime of beds occurs in 2020 (1,6 days) and 2021 (1,5 days). Such a jump in the indicator is most likely associated with the forced of beds re-profiling.Conclusions. Analysis of indicators of the use of beds in the City Clinical Hospital No. 1 named after N. I. Pirogov in the period 2012–2021. showed that in general there is an increase in the efficiency of the hospital. Therefore, it is necessary to constantly analyze the main statistical indicators in order to identify errors early and develop ways to solve them.